Estudo de proteínas de Angiostrongylus cantonensis para o entendimento da relação parasito-hospedeiro e análise de alvos para o diagnóstico das angiostrongilíases - Morassutti, Alessandra Loureiro (2011)
The genus Angiostrongylus Kamensky, 1905 belongs to the Phylum Nematode, with round shape as its main feature. Two species have medical importance, A. costaricensis living in mesenteric arteries of wild mice and causing abdominal angiostrongyliasis in human and A. cantonensis which lives in pulmonary arteries of rats and may cause eosinophilic meningoencephalitis in humans. The diagnosis of both diseases is difficult due to absence of parasite in feces in case of the infection by A. costaricensis and seldom detected larvae in the cerebrospinal fluid in case of eosinophilic meningoencephalitis. Several studies have been performed to improve the diagnosis of angiostrongyliasis which should be able to differentiate in a specific and sensitive way among other parasitic infections. The 31kDa antigen has been considered the main antigen for eosinophilic meningoencephalitis diagnosis due to A. cantonensis infection. However this antigen is obtained from crude extracts of the worm by a laborious process of purification with low yielding and insufficient amount for large distribution to other diagnostic centers. In order to improve the serologic diagnostic of angiostrongyliasis and make the antigens widely available the present work aimed to identify new antigenic targets and also characterize the 31kDa antigen for further recombinant production. Besides that, essential molecules for parasite survival were investigated which in the future may be targets for disease treatment. Two sources of antigen from female worms were used: excretion and secretion products (ES) and total extract (TE). In ES, sample antioxidant enzymes activity were detected such as catalase and superoxide dismutase. Also was identified by Western blot and Mass spectrometry (MS), 17 proteins target for disease diagnosis and treatment like hemoglobinases, heat shock proteins and proteases inhibitors. In TE sample antioxidant enzymes as well as glutathione transferases (GST) which is another kind of defense enzyme were also detected. GSTs were purified by affinity chromatography and analyzed by MS. Peptide sequences from this experiment matched with homologous sequences of sigma class GST. In TE samples was possible to characterize the 31kDa and after two-dimensional electrophoresis was shown to be composed of four spots around 4.5 of isoelectric point (pI) and being recognized by sera from patients infected with Angiostrongylus spp. The spots were analyzed by MS and three different proteins were identified: 14-3-3 protein, NAC domain containing protein, and epsilon subunit of the coatomer protein complex isoform 2. The 31kDa antigen was characterized as a glycoprotein through studies of oxidation of carbohydrate where it was observed that the antigenicity of four spots was dependent on sugar residues. The DNA sequences of the antigens were obtained by random sequencing of the genome for 454 platform (Roche) and deposited in Genbank. The data generated in this study contribute significantly to the development of recombinant antigens that may be widely distributed for independent diagnostic validation